Analysis of Temperature Distribution on the Coffee Roaster Drum for a Capacity of 2 kg Using Computational Fluid Dynamics (CFD) - Suryadi, Dedi; Leonanda, Benny Dwika; Mustagfirin, Alfin; Suandi, Agus (Jurnal Polimesin, 2024)
Coffee, one of Indonesia's largest commodities, is often processed using traditional methods and tools that rely heavily on manual labor and can be labor-intensive. To make the coffee roasting process more efficient and reduce the need for human effort, a coffee roasting machine can be used. This study aimed to analyze coffee roasting drums using computational fluid dynamics (CFD) to determine the optimal drum thickness and rotation speed in a coffee roasting machine. The study considered three different thicknesses (1mm, 2mm, and 3mm) and three different rotation speeds (60rpm, 65rpm, and 70rpm). The coffee roasting drum was modeled using CFD. The study's results showed that a drum thickness of 2mm and a rotation speed of 70rpm achieved the best heat distribution during roasting, reaching the desired temperature in 900 seconds. This information could be used to design a more efficient coffee roasting machine or improve the performance of existing machines.